Inheritance and molecular mapping of the genomic regions governing seed viability in soybean (Glycine max. L. Merr.): Inheritance and molecular mapping of the genomic regions governing seed viability in soybean (Glycine max. L. Merr.) - MANISHA SAINI; RAJU R YADAV; RAHUL KUMAR; MANU YADAV; N KRISHAN KUMAR RATHOD; MENIARI TAKU; SUDIPTA BASU; R AMBIKA RAJENDRAN; SK LAL; AKSHAY TALUKDAR (Journal of Oilseeds Research, 2023)
Loos of seed viability in soybean (Glycine max L. Merrill, 2n=40) during ambient storage from harvest to the next planting season is a significant barrier for the production of high-quality seeds. The present study includes the inheritance and molecular mapping of the loci linked to seed viability in soybean. For this, five high viable genotypes (>90% germination after one year of storage) viz. EC-1023, EC-105790, G2651, UPSL34, UPSL736 and three poorly viable genotype (